Prevalence and effect of myths in clinical orthopaedics in Western part of Uttar Pradesh - Vashisht, Arun; Rastogi, Avinash (International Journal of Research in Medical Sciences, 2017)
Background: Myths in the field of medicine regarding the treatment of health problems are frequently observed, which may not only retard the recovery but often be harmful for the patients. We were baffled to see lot of patients under the influence of certain myths about treatment of their orthopaedic ailments. The aim of this observational, prospective study was to dispel the misconceptions and to create awareness in the society about the bad effects of these myths. Methods: 1285 patients aged 20-55 years, suffering from fractures, neck pain, backache, osteoarthritis knee, myofascial trigger points, episacroiliac lipomas etc. and being under the influence of one or the other myth about the treatment of their ailments, were included in this study. Results: All Patients were counseled and made to realize the harmful effects of their false beliefs regarding treatment of their orthopaedic ailments. Every patient was treated as necessitated for the ailment. All patients were found satisfied at the end of treatment, and were happy after dispelling their myths. Conclusions: Misconceptions do not have any scientific basis rather these are rooted in the society due to high rate of illiteracy and lack of health education. Being a part and parcel of the health care system, it becomes our duty to create awareness among patients about the harmful effects of the prevailing false beliefs by imparting proper health care advice and treatment to relieve the sufferings of our patients.